Kiai's leadership in human resource management of islamic boarding schools in jambi indonesia - Al Hudori; Ahmad Husein Ritonga; Kasful Anwar; Hidayat, Wildan Nur; Hidayat, Al Mukaromah (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study aims to analyze kiai leadership and factors that hinder human resource management in Islamic Boarding Schools in Jambi. This research uses a descriptive qualitative study that reveals, finds and explores information about kiai leadership in HR Management of Islamic Boarding Schools in Jambi Province. Human resource management of Islamic boarding schools in Jambi Province is carried out with several stages. 1) Planning begins with recruiting the required HR without referring to HR recruitment patterns from professional institutions; 2) Organizing the placement of educators and education personnel in their fields of work despite overlapping positions; 3) Implementation, in accordance with the workflow, although some HR have duplicate jobs which result in not maximizing the work they carry out; 4) Controlling, as a control step from the implementation in the field, although the stages of control have not been clearly illustrated; 5) Assessment is carried out periodically even though it is according to the needs and desires of the leadership, so that the evaluation results cannot be used as guidelines in determining the next program. The causes of inhibiting factors in human resource management at Islamic boarding schools in Jambi have not been effective, among others: 1) HR professionalism has not been evenly distributed, Islamic boarding school HR prioritizes experience in working; 2) budget funds, facilities and facilities that support performance have not all met proper education standards in accordance with the mandate of laws and regulations; 3) As well as HR welfare has not met wage standards.